PENGARUH KINERJA KEUANGAN PADA RESPON INVESTOR - Prasetyo, Allan Daddy; Riduwan, Akhmad (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
This research is meant to find out the influence of financial performance which is represented by price earnings ratio, return on assets and return on equity to the respond of investors. The population includes of textile and garment companies which are listed in Indonesia Stock Exchange in the years of 2009-2013. This research has been done by using purposive sampling criteria and 10 go public textile and garment companies have been selected as samples. The data collection technique has been carried out by using secondary data from the Indonesia Stock Exchange. The data analysis method has been done by using multiple linear regressions analysis. The result of this research shows that (1) price earnings ratio has influence to the stock return of the company because it can become the determinant of stock price since it can predict the profit growth in the future, (2) return on assets has influence to the stock return of the company because the investors has considered this ratio is relevant to calculate the profit which has been generated by the assets which is owned by the company (3) return on equity has influence to the stock return of the company, this ratio shows the capability of the company to generate the net profit by using the capital which is owned by the company.Keywords: Price Earning Ratio, Return On Assets, Return On Equity and Return.